Botanical biopesticides: research and development trends, a focus on the Annonaceae family - Giraldo-Rivera, Ana Isabel; Guerrero-Alvarez, Gloria-Edith (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
This document analyzed research and development trends related to chemical, biological and economical biopesticides based on plant extracts, with emphasis on the Annonaceae family. A systematic review of the literature between 1947 and 2018 was done with an advance search equation in a specialized data base. This paper contains the development of plant bio pesticides, their modes of action, the more prominent families according to their bioactivity and the secondary metabolites that exert control over pests that are significant in agriculture and public health. The dynamics of publications, at the national and international levels, were identified, along with the countries that lead research, patents assigned in the last 20 years, market trends and bio pesticide regulation. The reviewed research is relevant to bioprospecting plant extracts with potential insecticidal activity and to the subsequent development of biocides using botanical extracts; the Annonaceae family is promising.